2018
DOI: 10.19082/6333
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of internet addiction based on information literacy among students of Iran University of Medical Sciences

Abstract: BackgroundA considerable group of internet users consists of university users; however, despite internet benefits and capabilities, internet overuse is a threat to societies especially to young people and students.ObjectiveThe objective of this study was to determine the predictive role of information literacy in internet addiction among students of Iran University of Medical Sciences during 2016.MethodsThis analytical cross-sectional study was conducted in Iran University of Medical Sciences in 2016. Using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…The results showed that the largest number of participants were in the age groups 30–40 and 20–30 years old, and the number of old participants was low, which could be due to lack of literacy, lack of mobile and internet facilities, and unwillingness to complete the questionnaire electronically. Studies have shown that the majority of internet users in Iran and worldwide comprise younger age groups (Keykhaie et al 2014 ; Langarizadeh et al 2018 ; Salehi et al 2014 ). This was in line with similar studies (Abdelhafiz et al 2020 ; Gu et al 2015 ; Zhong et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the largest number of participants were in the age groups 30–40 and 20–30 years old, and the number of old participants was low, which could be due to lack of literacy, lack of mobile and internet facilities, and unwillingness to complete the questionnaire electronically. Studies have shown that the majority of internet users in Iran and worldwide comprise younger age groups (Keykhaie et al 2014 ; Langarizadeh et al 2018 ; Salehi et al 2014 ). This was in line with similar studies (Abdelhafiz et al 2020 ; Gu et al 2015 ; Zhong et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate was higher than previous Iranian studies. For instance, the prevalence rate of IA was 31.2% in a study by Langarizadeh et al [29], 28.8% in a study by Nemati [30], 27.5%, in the Gorgich study [31], and 9.6% in the Bazrafshan et al study [32]. In the metaanalysis by Modara et al [11], the IA prevalence rate was 20% in Iran [16%-25% with a 95% confidence interval].…”
Section: Discussionmentioning
confidence: 99%
“…Iran is currently ranked first on internet use in the Middle East [12]. An IA problem is possible among Iranian adults; however, previous studies mainly targeted adolescents or university students in this area [13]. Besides, few studies explored IA among Iranian adults.…”
Section: Introductionmentioning
confidence: 99%